An analysis of the role of neighbourhood ethnic composition in the geographical distribution of racially motivated incidents - Sampson, Alice; Tsui, Hoi Yuen; Ralphs, Martin P. (The British journal of criminology, 2001)
This paper explores the use of statistical and Geographical Information Systems mapping techniques in producing a preliminary assessment of geographical patterns of racially motivated crimes and harassment in a given area. The geographical distribution of allegations of racially motivated incidents reported to the police in the London Borough of Newham is investigated. The results of the analysis suggest that the ethnic composition of an area appears to have a significant effect on the rate of incidents. Correlation and regression analyses are carried out and support the preliminary finding that rates of incidence are significantly higher where there is a large white majority and smaller groups of other ethnicities